A mediação do “sacerdote tradicional” dos Vatshwa e do presbítero católico nos ritos das orações pelos defuntos na igreja em Moçambique - Simone, Pedro Francisco (2022)
The issue of this research arises from the pastoral experience as a priest in the diocese of Inhambane, Mozambique. The theme encompasses, in a transversal way, the areas of African Traditional Religions (ATR) and Catholic theology in the liturgical-pastoral dimension of the Sacrament of Order; specifically in the presbyteral degree. The study presents the relationship between the “traditional priest” of the vatshwa and the Catholic priest regarding the functions performed in the prayer for the dead, by the two characters highlighted in the present work. The ecclesiological historiography of Mozambique is briefly discussed, from the first initial presence of the missionaries to the current phase. Next, there is a description of the functions of the “traditional priest” in the rite of the funeral in the context of the vatshwa. In fact, it is essential to keep in mind that this priest is part of the clan; it is not an unknown person. His ascension to this category is not by vocation, but by right or by indication of ancestors. The priestly ministry is also described in its scope and then focused on a man called to pray for the dead. Thus, the research shows similarities and differences between the “traditional priest” and the Catholic priest. In this research it was concluded that the pastoral problems related to prayer for the dead are largely due to the failures of the first evangelization regarding the understanding of African culture on the part of catholic missionaries.